Antiphospholipid Antibodies and Their Association with Atherosclerotic Changes in Patients with Systemic Lupus Erythematosus – Review of Literature and Own Experiences - Fischer, Katarzyna; Flicinnski, Jacek; Brzosko, Marek (IntechOpen, 2012)
None